Strategi Supply Chain Usaha Kecil dan Menengah (UKM) Dalam Menghadapi Pasar Bebas (Studi Kasus PAUB, Malang, Indonesia) - Ahmad Hidayat Sutawijaya (Indonesian Journal of Cultural and Community Development, 2018)
This article puts forward the strategy of supply chain strategy for small and medium enterprises (called SMEs) in developing the network during their business period which network is needed and will change from time to time. Successful implementation of supply chain management (SCM) can give SMEs an advantage over their competitors. Problems that occur for SMEs in Indonesia and other developing countries face problems in the implementation of SCM due to lack of resources and direction. To compete effectively in global markets, SMEs must have effective supply chain management and thus require comprehensive strategic planning in an effort to develop the SME business group itself. This research methodology used qualitative approach through interview approach and field study to group members of Women Interfaith Among Religious (PAUB), Malang city. The results of field studies show that integrated small and medium enterprise (SME) supply chain strategy planning contribute to the success of SMEs for PAUB members of Malang city. The supply chain strategy planning process that SMEs need has stages like "source," "create," and "deliver". Thus, when implemented it will connect with various supply chain cycles such as "ordering," "procurement," "production," "distribution," and "customer" for SME groups.